Functional magnetic resonance imaging studies of acupuncture at ST36: a coordinate-based meta-analysis - Zhang, Jinhuan; Liu, Yongfeng; Li, Zihan; Hu, Qingmao; Huang, Xingxian; Lv, Hanqing; Xu, Jinping; Yu, Haibo (Frontiers in Neuroscience, 2023)
Background: Functional magnetic resonance imaging (fMRI) has been widely used to investigate brain effect of Zusanli(ST36). However, the inconsistent results have hindered our understanding of the exact brain effect of ST36. Objective: To perform a meta-analysis of fMRI studies about acupuncture at ST36 to assess brain atlas of acupuncture from available studies. Method: Based on a preregistered protocol in PROSPERO (CRD42019119553), a large set of databases were searched up to August 9, 2021, with no language restrictions. Peak coordinates were extracted from clusters that showed significant signal differences between before and after acupuncture treatment. Meta-analysis was performed using seed-based d mapping with the permutation of subject images (SDM-PSI), a newly improved meta-analytic method. Results: Twenty-seven studies (27 ST36) were included. This meta-analysis found that ST36 could activate left cerebellum, bilateral rolandic operculum, right supramarginal gyrus, and right cerebellum. Functional characterizations showed that ST36 mainly associated with action and the perception. Conclusion: Our results provide brain altas for ST36, which not only offered a better understanding of the underlying neural mechanism, but also provided the possibility for future precision therapy.